Recent Advances in Silver Nanowires Electrodes for Flexible Organic/Perovskite Light-Emitting Diodes - Hou, Shuping; Liu, Jie; Shi, Feipeng; Zhao, Guo-Xu; Tan, Jia-Wei; Wang, Gong (Frontiers in Chemistry, 2022)
Flexible organic light-emitting diodes and perovskite light-emitting diodes (PeLEDs) have been investigated as an innovative category of revolutionary LED devices for next-generation flat display and lighting applications. A transparent conductive electrode is a key component in flexible OLEDs and PeLEDs, and has been the limitation of the development in this area. Silver nanowires (AgNWs) have been regarded as the most suitable alternative material in TCEs, due to the economical solution synthesis and compatibility with roll-to-roll technology. This mini-review addresses the advances in silver nanowires electrodes for flexible organic/perovskite light-emitting diodes, and the relationship between electrode optimization and device performance is demonstrated. Moreover, the potential strategies and perspectives for their further development of AgNWs-based flexible OLEDs and PeLEDs are presented.